Editorial Board and Table of Contents - Sausverde, Ērika; Steponavičiūtė, Ieva (Scandinavistica Vilnensis, 2014)
In May 2012, the Centre of Scandinavian Studies at Vilnius University marked its 20 year anniversary by holding an international scholarly conference – Feast, Play and Puzzles in Scandinavian Studies. The event drew together students and teachers of the Centre – present and former, and welcomed many guests from other universities and public institutions. The Conference was a real feast for the mind, in the form of excellent papers, an engaging students’ poster session and vivid discussions. It showed that modern Scandinavian Studies are a diverse and vibrant academic field, posing riddles and puzzles to those who are active in it, but also rewarding them with the joy of new discoveries. The present collection of articles is, for the most part, based on papers delivered at the conference and reworked especially for this publication. With a few more articles added, it covers different areas of Scandinavian linguistics, mythology, literature and sociology. We would like to heartily thank everyone who took part in the conference and/or contributed to the present collection. We are grateful to the authors for sharing their scholarly findings with us, and for their patience and good will waiting for this book to appear. Special thanks go to the reviewers and the members of the editorial board of Scandinavistica Vilnensis for all their comments and wisdom. Last but not least, we express our gratitude to The Letterstedt Association and the Faculty of Philology of Vilnius University for the financial support to publish this book. Sincerely yours Ērika Sausverde & Ieva Steponavičiūtė